Cost and return analysis of milkfish operations in different farm sizes in Barotac Nuevo, Iloilo - Belgira, Gay Nanette (1996.)
Milkfish (Chanos chanos) is the most imporant pond culture fish specie in the Philippines, Barotac Nuevo, where the study conducted, is among the most productive in the province of Iloilo in terms of milkfich culture., Cost and Return Analysis of Milkfish Production evaluated the economic performance of 30 milkfish farms in Barotac Nuevo. The economic performance of milkfish farms were assessed using profit, revenue, return on investment, rate of return on operating cost, and payback period. Investment and cost structure were also presented. Comparative analysis was done by farm size namely; small farms (less than 5ha), medium farms (5.01 to 20ha) and large farms (above 20 ha). Farm investment increased as farm size increased. The highest yield per hectare per crop was obtained by medium farms (708.86 kg.) followed by large farms (566.76 kg) and small farms (394.16 kg). For all farms, economic profit decreased as farm size increased on a per farm basis. Small farms had an economic profit of P7,525.25. Medium farms had P55,157.66 while large farms had P131,575.59. Results showed that variable cost of medium farms (21,056.97) on a per hectare basis was higher than that of the large farms (20,298.67) while fixed cost of all farms on a per hectare basis decreased as farm size increased. Opportunity cost of farms on a per hectare basis decreased as farm size increased. Small farms had the lowest return on investment (14.30%) followed by medium farms (30.68%) and large farms (42.31%). Rate of return on operating cost for small farms was 56.03% while medium farms had 26.53% and large farms had 13.4% Payback period of all farms decreased as farms size increased. Small farms had 6.99 years, medium farms had 3.29 years and large farms had 2.36 years. From all economic indicators presented, milkfish pond culture remains a profitable business venture in Barotac Nuevo. Small farms were found to be productive due to the close farm supervision devoted by owners themselves, but medium farms were found to be the most profitable farm size to operate in milkfish pond culture in Barotac Nuevo. Large farms has lower yield because of the large area it occupies that an operator can hardly check all areas.
Thesis (Undergraduate, Bacholer of Arts in Economics) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo 1996.
Keywords: Milkfish farming -- Barotac Nuevo, Iloilo .